Lüge und Täuschung in den Zeiten von Putin, Trump & Co. - König, Helmut (transcript, 2020)
Putin and Trump are currently considered the most powerful men in the world. Both continuously resort to lies, deceptions and tricks in their political practice, not only towards their own populations, but also in international relations. Why do they do this and why do they succeed in doing so? And is it at all different from common practice in politics anyway anywhere in the world? Helmut König undertakes a general analysis of the meaning of truth and lies in politics and provides many examples of the practice of lying in Trump's America and Putin's Russia.